Essential role for smooth muscle cell stromal interaction molecule-1 in myocardial infarction. Issue 2 (February 2018) - Mali, Vishal; Haddox, Samuel; Belmadani, Souad; Matrougui, Khalid
Abstract : Objectives: Stromal interacting molecule-1 (STIM1) plays a role in coordinating calcium signaling in different cell types. The increase or deletion of STIM1 expression in cardiomyocyte causes cardiac complication. Moreover, the deletion of STIM1 in endothelial cell causes vascular endothelial dysfunction. However, the disruption of STIM1 in smooth muscle cells (SMC) has no effect on endothelial function but protects vascular function when mice are infused with angiotensin-II. Nevertheless, the role of SMC-STIM1 in acute and chronic myocardial infarction (MI) induced by acute ischemia–reperfusion injury and permanent coronary artery occlusion is unknown. Methods and results: Stim1 fl/fl were generated and crossed into the SM22α-Cre + backgrounds. SM22α-Cre + causes deletion of STIM1 floxed genes in adult SMC (Stim1 SMC−/− ). Control and Stim1 SMC−/− mice were subjected to acute ischemia–reperfusion injury. Hearts were then harvested and incubated with triphenyltetrazolium chloride to determine the infarct size. In control mice which are subjected to ischemia–reperfusion, the heart developed a significant infarct associated with an increase in STIM1 expression. Interestingly, the infarct size was substantially reduced in Stim1 SMC−/− mice. The protection in Stim1 SMC−/− mice against ischemia–reperfusion injury involves the modulation of endoplasmic reticulum stress, apoptosis, oxidative stress, protein kinase B, and mitogen-activated protein (MAP) kinase (ERK1/2 and p38) signaling, and inflammation. Furthermore, in another model of chronic MI induced by permanent coronary artery occlusion, SMC-STIM1 disruption significantly reduced myocardial infarct size and improved cardiac function. Conclusion: Our results provide new evidence that SMC-STIM1 disruption is a novel mechanism that protects the heart from MI through reduction of endoplasmic reticulum stress, oxidative stress, MAP-Kinase, apoptosis, and inflammation.